Another origin of the Theology of Hope? Moltmann's dependence on Mircea Eliade1. (February 2017) - Coombe, Cameron
The influence of Mircea Eliade on Moltmann's work has largely been overlooked in scholarship. This article seeks to address this, providing an exposition of the themes of history and historicism in Eliade's work and demonstrating how Moltmann draws upon these to develop his concept of 'epiphany religion', especially in Theology of Hope but also at later stages in his career. Eliade's scholarship also bolsters Moltmann's claims regarding the uniqueness of promissory history in its contention that non-Judeo-Christian societies reject history in the same way that 'Greek' society does, allowing Moltmann to situate his polemics against Greek philosophy in a universal context, and giving Moltmann's theological claims an air of respectability insofar as they are supported by secular scholarship. The second part of the article critically evaluates Moltmann's dependence on Eliade in regard to generalized claims in both of their works.